1995
DOI: 10.1073/pnas.92.17.8055
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for long-term expression of erythropoietin in rats.

Abstract: The injection of recombinant erythropoietin (Epo) is now widely used for long-term treatment of anemia associated with chronic renal failure, cancer, and human immunodeficiency virus infections. The ability to deliver this hormone by gene therapy rather than by repeated injections could provide substantial clinical and economic benefits. As a preliminary approach, we investigated in rats the expression and biological effects of transplanting autologous vascular smooth muscle cells transduced with a retroviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…On the other hand, continuous Epo delivery by 400 g of pCAGGS-Epo resulted in the down-regulation of endogenous Epo induction (P = 0.42) even after phlebotomy, consistent with previous reports by us 6 and another group. 14 These data indicate that a sufficient dose of pCAGGS-Epo down-regulated the endogenous Epo production for as long as 11 weeks and that erythrocytosis induction was mediated by vector-encoded Epo secretion, although there is another possibility that increased endogenous Epo synthesis occurred in phlebotomized animals but overall levels of Epo protein, endogenous plus ectopic, were not detected because of Epo clearance or excretion. The rats were immediately killed after this phlebotomy experiment.…”
Section: Induction Of Endogenous Epo Production By Phlebotomymentioning
confidence: 80%
“…On the other hand, continuous Epo delivery by 400 g of pCAGGS-Epo resulted in the down-regulation of endogenous Epo induction (P = 0.42) even after phlebotomy, consistent with previous reports by us 6 and another group. 14 These data indicate that a sufficient dose of pCAGGS-Epo down-regulated the endogenous Epo production for as long as 11 weeks and that erythrocytosis induction was mediated by vector-encoded Epo secretion, although there is another possibility that increased endogenous Epo synthesis occurred in phlebotomized animals but overall levels of Epo protein, endogenous plus ectopic, were not detected because of Epo clearance or excretion. The rats were immediately killed after this phlebotomy experiment.…”
Section: Induction Of Endogenous Epo Production By Phlebotomymentioning
confidence: 80%
“…33 However, we showed that the same promoters in retroviral vector constructs permitted stable gene expression for several months in transduced hematopoietic stem cells 34,35 and smooth muscle cells. 16,18,22 These data suggested tissue-specific vector inactivation. When fibroblasts are in a quiescent state the choice of promoter for the transduced gene was a major determinant for long-term in vivo gene expression.…”
Section: -11mentioning
confidence: 92%
“…15 Smooth muscle cells are present within the vasculature as a multilayered mass of long-lived cells in proximity to the circulation and have been investigated as targets for gene therapy. [16][17][18][19][20][21][22] In vivo gene expression from transduced keratinocyte implants has also been studied. [23][24][25] Retrovirus-mediated gene transfer into primary skin fibroblasts has provided measurable amounts of therapeutic proteins in animal models, including adenosine deaminase (ADA), 26,27 factor IX, 28,29 ␤-glucuronidase 30,31 and erythropoietin.…”
Section: -11mentioning
confidence: 99%
“…Other than cell death, this effect may be due to a suppression of the endogenous production of EPO. 12 However, when cells were vehicled by a 3D scaffold, the increased level of hematocrit was maintained for a much longer period of time, up to 14 weeks. Cells recovered from the implants, after the hematocrit had returned to a normal level, were able to grow in vitro and to secrete EPO although at an efficiency of 50%.…”
Section: Figure 6 Microphotographs Of Histological Sections Of Retriementioning
confidence: 99%